Humoral and cellular immunity of two‐dose inactivated COVID‐19 vaccination in Chinese children: A prospective cohort study. Issue 1 (19th December 2022) - Wang, Hao; Gan, Mengze; Wu, Bihao; Zeng, Rui; Wang, Zhen; Xu, Jun; Li, Jia; Zhang, Yandi; Cao, Jinge; Chen, Li; Di, Dongsheng; Peng, Siyuan; et al.
Abstract: Children are the high‐risk group for COVID‐19, and in need of vaccination. However, humoral and cellular immune responses of COVID‐19 vaccine remain unclear in vaccinated children. To establish the rational immunization strategy of inactivated COVID‐19 vaccine for children, the immunogenicity of either one dose or two doses of the vaccine in children was evaluated. A prospective cohort study of 322 children receiving inactivated COVID‐19 vaccine was established in China. The baseline was conducted after 28 days of the first dose, and the follow‐up was conducted after 28 days of the second dose. The median titers of receptor binding domain (RBD)‐IgG, and neutralizing antibody (NAb) against prototype strain and Omicron variant after the second dose increased significantly compared to those after the first dose (first dose: 70.0, [interquartile range, 30.0–151.0] vs. second dose: 1261.0 [636.0–2060.0] for RBD‐IgG; 2.5 [2.5–18.6] vs. 252.0 [138.6–462.1] for NAb against prototype strain; 2.5 [2.5–2.5] vs. 15.0 [7.8–26.5] for NAb against Omicron variant, all p < 0.05). The flow cytometry results showed that the first dose elicited SARS‐CoV‐2 specific cellular immunity, while the second dose strengthened SARS‐CoV‐2 specific IL‐2 + or TNF‐α + monofunctional, IFN‐γ + TNF‐α + bifunctional, and IFN‐γ − IL‐2 + TNF‐α + multifunctional CD4 + T cell responses ( p < 0.05). Moreover, SARS‐CoV‐2 specific memory T cells were generated after the first vaccination, including the central memory T cells and effector memory T cells. The present findings provide scientific evidence for the vaccination strategy of the inactive vaccines among children against COVID‐19 pandemic.